Sebuah Penggunaan YouTube Sebagai Alat dalam Pembelajaran Bahasa Inggris: Meta Analisis: Meta Analisis - Salsabila, Dhea Arinda; Salam, Urai; Rezeki, Yanti Sri (English Education:Journal of English Teaching and Research, 2025)
The purpose of this study was to investigate the use of YouTube as a tool for English language learning in secondary and university settings within English as a Foreign Language (EFL) contexts. The study included 81 empirical research journal papers published between 2015 and February 2024. The researchers evaluated article journals that met the criteria for inclusion in the review to gain insights into the utilization of YouTube in English Language Learning (ELL) in both university and secondary school settings, with a particular focus on its use in the EFL context. This study employed a simple statistical and analytical framework to analyze the existing data. The findings revealed that the most enhanced skill using YouTube was speaking. The initial number of articles obtained at the beginning of the process was 1054 articles. Then, screening was conducted according to the inclusion criteria and based on PRISMA, resulting in a final total of 81 articles. Calculations were performed by computing the effect size of each article individually and then averaging all of them using Microsoft Excel. The mean effect size from 81 articles is 1.24, indicating a very high impact on the use of YouTube as a tool for English language learning. The results also showed that the utilization of YouTube was categorized into platforms for producing content, flipped classroom, discussion platform, and media platform. Pedagogical and theoretical implications were suggested.